Teaching English through pedagogical translanguaging - Cenoz, Jasone; Gorter, Durk (World Englishes, 2020)
Teaching English has traditionally been associated with a monolingual bias and the exclusive use of English in the classroom is highly recommended in different countries. Nowadays English is widely used to teach academic content and this strict separation of languages can be problematic because it prevents students from using resources they have previously acquired in other languages (Cenoz & Gorter, 2015; Kubota, 2018). In this article we discuss ‘pedagogical translanguaging’ understood as intentional instructional strategies that integrate two or more languages and aim at the development of the multilingual repertoire as well as metalinguistic and language awareness. Pedagogical translanguaging considers learners as emergent multilinguals who can use English and other languages depending on the social context. Their linguistic resources are valued and learners are not seen as deficient users of English but as multilingual speakers.